2012
DOI: 10.1617/s11527-012-9858-6
|View full text |Cite
|
Sign up to set email alerts
|

Inductive method for assessing the amount and orientation of steel fibers in concrete

Abstract: Steel fibers are ferromagnetic and they\ud have the property of altering the magnetic field around\ud them. This paper discusses a method and gives a\ud practical example to measure, non-destructively, the\ud amount and orientation of fibers from cubic concrete\ud specimens (150 mm). This is possible because the\ud fibers affect inductance of a sensor (an inductive coil)\ud that is wrapped around the specimen.Peer ReviewedPostprint (published version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 20 publications
2
61
0
6
Order By: Relevance
“…Such electromagnetic methods can be used either for laboratory specimens or small elements (Torrents et al, 2012) or for real size structures The fiber distribution in precast elements, in an industrial setting, was studied using drilled cores from the FRC, with the fiber orientation determined using X-ray analysis and the fiber content determined by crushing the cores. Using this technique, Kooiman (2000) studied the fiber orientation and distribution in precast tunnel lining segments reinforced with 60 kg/m 3 of steel fibers and concluded that the fibers were not randomly oriented spatially and that bleeding was observed during vibration of the segment, which causes differences in the concrete quality over the thickness of segment, resulting in variations in the FRC properties.…”
Section: Fiber Distribution In the Frcmentioning
confidence: 99%
“…Such electromagnetic methods can be used either for laboratory specimens or small elements (Torrents et al, 2012) or for real size structures The fiber distribution in precast elements, in an industrial setting, was studied using drilled cores from the FRC, with the fiber orientation determined using X-ray analysis and the fiber content determined by crushing the cores. Using this technique, Kooiman (2000) studied the fiber orientation and distribution in precast tunnel lining segments reinforced with 60 kg/m 3 of steel fibers and concluded that the fibers were not randomly oriented spatially and that bleeding was observed during vibration of the segment, which causes differences in the concrete quality over the thickness of segment, resulting in variations in the FRC properties.…”
Section: Fiber Distribution In the Frcmentioning
confidence: 99%
“…The equipment proposed by Torrents et al [1] is composed by a discontinuous square coil manufactured with a copper cable of 0.2 mm of diameter and a length of 1600 mm, resulting in a total of 2354 turns. The dimensions of the prismatic plastic element around which the coil is placed are 15 x 17 x 17 cm (see Figure 1.a).…”
Section: Figure 2 Fibres Inside a Non-homogeneous Magnetic Flux (A) mentioning
confidence: 99%
“…The increasing use of steel fibre reinforced concrete (SFRC) [1][2][3][4] has generated the need for tests that provide information about the material. Besides the traditional tests to assess mechanical properties [5][6][7], different techniques are required to evaluate the fibre content and orientation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations